A Cross-sectional Study on Evidence-Based Nursing Practice in the Contemporary Hospital Setting: Implications for Nurses in Professional Development. Issue 2 (March 2017) - Rose Bovino, Leonie; Aquila, Anne M.; Bartos, Susan; McCurry, Tina; Cunningham, C. Elizabeth; Lane, Todd; Rogucki, Nicole; DosSantos, Jamie; Moody, Danielle; Mealia-Ospina, Karen; Pust-Marcone, Jancee; Quiles, Jonathan
Abstract : Evidence indicates that nurses inconsistently engage in evidence-based practice (EBP). This cross-sectional study of 402 nurses at a medical-surgical hospital identifies strategies for augmenting EBP. Nurses' EBP beliefs scores were higher than their EBP implementation scores. Those with baccalaureate/postgraduate degrees had higher EBP beliefs and implementation scores than those with associate degrees or diplomas. Bedside or direct care nurses were less likely to have baccalaureate/higher degrees and had lower EBP beliefs and implementation scores than did those nurses not serving in direct care roles.